Effects of mindfulness meditation on sleep, stress, and athletic coping skills of female collegiate athletes - Sharp, C. (California State University, 2024)
This study sought to investigate the effects of a 6-week daily mindfulness meditation on the stress, sleep, and athletic coping skills of female college athletes. Four National Collegiate Athletic Association (NCAA) female athletes were recruited to participate. A multiple subject case study research design utilizing mixed methods was employed. Quantitative measurement tools included the Perceived Stress Scale (PSS; Cohen et al., 1983), the Pittsburgh Sleep Quality Index (PSQI; Buysse et al., 1989), the Athletic Coping Skills Inventory (ACSI; Smith et al., 1995) and sleep logs, and qualitative measurement tools included mindfulness meditation journals and a postintervention questionnaire. Results showed no significant changes in stress levels but significant improvements in sleep quality (t(3) = 2.63, p = 0.039), athletic coping skills (t(3) = -2.58, p = 0.041), and total time in bed (t(3) = -3.41, p = 0.021). There was also an overwhelming positive response from all participants in the qualitative findings. This suggests that mindfulness can improve sleep quality and athletic coping skills, which have been linked to improved health and performance respectively (Christensen & Smith, 2018; Watson, 2017). The all-female participant group in this study also assisted in closing the gender gap in sport science research helping to create a more equitable sport environment in which women can thrive (Cowley et al., 2021; Emmonds et al., 2019). This study revealed the ability of a simple mindfulness practice to potentially improve stress, sleep, and athletic performance in female college athletes.